Hubungan antara beban kerja dengan tingkat keluhan kerja pada pekerja kuli panggul di pasar salak banjarnegara - Eka Desi Yuliana; Rakhmat Susilo (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2020)
Objective: This study aims to determine the relationship between workload and the level of work complaints in the porters in the Salak Market in Banjarnegara. Methods: This is a quantitative research using analytic observational methods. Cross Sectional approach was used as the design in this study. The total sampling was used as the sampling method. Chi Square was used to test the data. Results: It is found that the category of workload and the level of work complaints on market porters are in the medium workload with a low complaint level by 20 respondents (76.9%) with the results of the p value (0.021<0.05). Therefore, there is a correlation between workload and the level of work complaints on the porters in the Salak Market in Banjarnegara. Conclusion: There is a correlation between workload and the level of work complaints on the porters in the Salak Market in Banjarnegara.Keywords: Workload, Work Complaints, Porters